Crystal Structure and Magnetic Properties of TbTSn Compounds (T = Pt and Rh) - Doan, Ho Thi; Hiep, Vuong Van; Thuan, Nguyen Khac; Anh, Do Thi Kim (VNU Journal of Science: Mathematics - Physics; Vol 34 No 2, 2018)
The TbTSn compounds (T = Pt, Rh) have been prepared by arc-melting in purified Ar atmosphere. Crystal structures were studied by X-ray powder diffraction. The Rietveld analysis shows the single phase in hexagonal ZrNiAl-type structure for TbPtSn and TbRhSn compounds. Magnetic properties and specific heat measured by mean of Physical Properties Measurement System (PPMS) demonstrated the phase magnetic transition at Néel temperature TN. Keywords Crystal structure, Magnetic properties References [1]. A. Szytula, and J. Leciejewicz, Handbook of the Crystal Structure and Magnetic Properties of Rare Earth Intermetallics, CRC, Boca Reton, 1994, pp.83-98. [2]. P. Rogl, Handbook of Physics and Chemistry of Rare Earth, eds. K.A. Gschneider Jr. and L. Eyring North-Holland, Amsterdam, 1984, Vol. 7, p. 1. [3]. T. Fujita, T. Suzuki, S. Nishigori, T. Tahabakete, H. Fujii and J. Sakurai, J. Magn. Magn. Mater. 108, 35 (1992). [4]. C.D. Routsi, J.K. Yakinthos, and E. Gammari-Seale, J. Magn. Magn. Mater. 110, 317 (1992). [5]. M. Kurisu, H. Hori, M. Furusawa, M. Miyake, Y. Andoh, I. Oguro, et al., Physica B 201 (1994) 107. [6]. Y. Andoh, M. Kurisu, S. Kawano, Physica B 237–238 (1997) 575. [7]. S. Kawano, Y. Andoh, M. Kurisu, J. Phys. Chem. Solids 60 (1999) 1205. [8]. M. Kurisu, R. Hara, G. Nakamoto, M. Furusawa, H. Hori, S. Kawano, et al., Rev. High Pressure Sci. Technol. 7 (1998) 550. [9]. M. Kurisu, G. Nakamoto, T. Nobata, T. Ida, T. Tsutaoka, Y. Andoh, et al., KURRI Prog. Rep. 43 (1999) 13. [10]. M. Kurisu, G. Nakamoto, T. Himi, Y. Andoh, T. Tsutaoka, S. Kawano, Activity Rep. Neut. Scatt. Res., ISSP Univ. Tokyo 8 (2001) 147. [11]. J. Sakurai, Y. Yamaguchi, K. Mibu, T. Shinjo, J. Magn. Magn. Mater. 84 (1990) 157. [12]. D.T. Adroja, S.K. Malik, Phys. Rev. B 45 (1992) 779. [13]. M. Guillot, A. Szytu"a, Z. Tomkowicz, R. Zach, J. Alloys Comp. 226 (1995) 131. [14]. H. M. Rietveld: Acta Crystallogr. 22 (1967) 151. [15]. A. Szytula, M. Kolenda, J. Leceijewicz, and N. Süsser, J. Magn. Magn. Mater. 164, 377 (1996). [16]. Yoshikazu Andoh, Do Thi Kim Anh, Hiroyuki Hoshino, Go Nakamoto, Makio Kurisu, Shinji Kawano, Physica B 373 (2006) 150–153.